An Integrative Pan-Cancer Analysis Revealing MLN4924 (Pevonedistat) as a Potential Therapeutic Agent Targeting Skp2 in YAP-Driven Cancers - Lan, Chungen; Ni, Bo; Zhao, Tiansuo; Li, Zekun; Wang, Junjin; Ma, Ying; Li, Weidong; Wang, Xiuchao (Frontiers in Genetics, 2022)
Background: YAP, coded by YAP1 gene, is critical in the Hippo pathway. It has been reported to be involved in the tumorigenesis and progression of several cancers. However, its roles on tumor cell proliferation in diverse cancers remain to be elucidated. And there is currently no clinically feasible drug that can directly target YAP in cancers. This research aimed to explore the regulatory mechanism of YAP in promoting tumor proliferation of multiple cancers, in order to find new strategies for inhibiting the overgrowth of YAP-driven cancers. Methods: We investigated the expression pattern of YAP1 in pan-cancer across numerous databases and our cohorts. First, univariate Cox regression analysis and survival analysis were used to evaluate the effect of YAP1 on the prognosis of cancer patients. Second, TIMER was used to explore the relationship between YAP1 expression and tumor cell proliferation. Third, functional and pathway enrichment was performed to search for targets of YAP involved in cell cycle in cancers. At last, GDSC and CCLE datasets were used to assess the correlation between SKP2 expression and MLN4924 IC50. Results: Differential expression analysis of multiple databases and qPCR validation showed that YAP1 was generally overexpressed in pan-cancers. Survival analysis revealed that YAP1 over-expression was significantly related to poor prognosis of patients with PAAD. The expression level of YAP1 was positively correlated with the proliferation in varieties of tumors. Further, SKP2 was confirmed as a target of YAP in promoting tumor cell proliferation. In addition, SKP2 expression was negatively correlated with MLN4924 IC50 values in almost all cancer types. Conclusion: YAP1 is frequently overexpressed in human cancers. YAP promoted tumor cell proliferation by up-regulating SKP2 expression in multiple cancers. The comprehensive pan-cancer analysis suggested that inhibition of Skp2 with MLN4924 might be an effective therapeutic strategy for attenuating tumor cell proliferation in YAP-driven cancers.